The Evolution of Suffering, Epiphenomenalism, and the Phenomena of Life: Evidential Problems for Naturalists - James D. Madden (Religions, 2021)
Paul Draper argues that the central issue in the debate over the problem of suffering is not whether the theist can offer a probable explanation of suffering, but whether theism or naturalism can give a better explanation for the facts regarding the distribution of pain as we find them. He likewise maintains a comparison of relative probabilities considering the facts of suffering; atheological naturalism is to be preferred. This essay proceeds in two phases: (a) It will be argued that mainstream positions in naturalistic philosophy of mind make it difficult to take pain as anything but epiphenomenal and therefore not subject to evolutionary explanation. While the distribution of suffering is a difficulty for the theist, the naturalist has equal difficulty explaining the fact that there is any suffering at all in the first place. Thus, the facts of suffering offer no advantage to the atheist. (b) Phenomenologists suggest that there is an intrinsic connection between animal life, pain, and normativity (including a summum bonum). The mere occurrence of life and normativity are, at least prima facie, more likely on the assumption of theism than atheism, so the theist may have a probabilistic advantage relative to the atheist. Phases (a) and (b) together support the overall conclusion that the facts of pain as we find them in the world (including that there is any pain at all) are at least as great, if not greater, a challenge for the atheist as they are the theist.